A Pharmacological study of Boerhavia Diffusa roots in the treatment of eye diseases (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The present research work aims to explore the therapeutic uses of root of Boerhavia diffusa in eye ailments particularly to evaluate its suitability as a topical formulation in the form of eye drops. The study utilised both the in vivo and in vitro techniques in order to assess the effectiveness and safety of the plant extract. Male adult Wistar albino rats were used in inducing cataracts and in the efficacy testing of the formulated eye drops. The study contrasted the outcomes of the Boerhavia diffusa-based eye drops against a traditional commerical eye drop known as Itone. Studies revealed that the herbal formulate did not cause any form of ocular irritation and also that there were possibilities of using this formulation to controlled formation of cataract. The lens opacity score analysis using photometry and lens morphology observation for 30 days showed that treatments with Boerhavia diffusa eye drops had less increase from the basal level and less fold increase compared to the control group. They hypothesize that this herbal preparation could be an effective Natural treatment option or an adjunct therapy for some eye afflictions especially cataract.